2017
DOI: 10.1007/s10666-017-9584-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Globalization Detrimental to CO2 Emissions in Japan? New Threshold Analysis

Abstract: Using annual data 1970Using annual data -2014, this paper examines the effects of globalization on CO2 emissions in Japan while accounting for economic growth and energy consumption as potential determinants of carbon emissions. The structural breaks and asymmetries arising due to policy shifts require attention and hence an asymmetric threshold version of the ARDL model is utilized. The results show the presence of threshold asymmetric cointegration between the variables. The threshold-based positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 209 publications
(87 citation statements)
references
References 47 publications
(63 reference statements)
12
69
0
6
Order By: Relevance
“…(2015) using a time series framework for India, found a significant role of economic growth for environmental quality. In contrast, Shahbaz et al. (2018b) found that economic growth deteriorates environmental quality in Japan.…”
Section: Literature Reviewmentioning
confidence: 94%
“…(2015) using a time series framework for India, found a significant role of economic growth for environmental quality. In contrast, Shahbaz et al. (2018b) found that economic growth deteriorates environmental quality in Japan.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The empirical results reveal that globalization increases carbon emissions, and thus the globalization-driven carbon emissions hypothesis is valid. Shahbaz et al (2017b) examine the effects of globalization on CO2 emissions in Japan by using annual data from 1970 to 2014 and an asymmetric threshold version of the ARDL model. They conclude that globalization significantly increases carbon emissions in Japan in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Composition effect has a direct link with economic activities and carbon emissions due to agricultural, industrial, and service sector pollution intensity. As the economy moves from agriculture to the industrial sector, carbon dioxide emissions increases, and when it advances from the industrial sector to service sector, it begins to decline (Shahbaz et al, 2018). Hence, globalization may have a significant impact on carbon dioxide emissions (environment degradation).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although advanced countries use high-energy-intensive technology in economic activities, they will still suffer from increasing carbon emissions generated by developing countries due to the closer integration of these economies at the global level through globalization (Shahbaz, Shahzad, & Mahalik, 2017;Shahbaz, Shahzad, Mahalik, & Sadorsky, 2018). It impacts energy consumption through its influence on production, consumption, and transportation of products as well as through the diffusion of technology across borders.…”
Section: Introductionmentioning
confidence: 99%
“…2 Eventually, the increasing carbon emissions linked with a massive energy use of developing countries will add to global carbon emissions. Thus, although advanced countries use high-energy-intensive technology in economic activities, they will still suffer from increasing carbon emissions generated by developing countries due to the closer integration of these economies at the global level through globalization (Shahbaz, Shahzad, & Mahalik, 2017;Shahbaz, Shahzad, Mahalik, & Sadorsky, 2018).…”
Section: Introductionmentioning
confidence: 99%